2017
DOI: 10.1186/s12889-017-4530-2
|View full text |Cite
|
Sign up to set email alerts
|

Medical Advice for Sick-reported Students (MASS) in intermediate vocational education schools: design of a controlled before-and-after study

Abstract: BackgroundSchool absenteeism, including medical absenteeism, is associated with early school dropout and may result in physical, mental, social and work-related problems in later life. Especially at intermediate vocational education schools, high rates of medical absenteeism are found. In 2012 the Dutch intervention ‘Medical Advice for Sick-reported Students’ (MASS), previously developed for pre-vocational secondary education, was adjusted for intermediate vocational education schools. The aim of the study out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…For this study, baseline and follow-up data from the Medical Advice for Sick-reported Students (MASS) intervention evaluation study were used, which is described in more detail elsewhere [20].…”
Section: Methodsmentioning
confidence: 99%
“…For this study, baseline and follow-up data from the Medical Advice for Sick-reported Students (MASS) intervention evaluation study were used, which is described in more detail elsewhere [20].…”
Section: Methodsmentioning
confidence: 99%
“…The program evaluation of the MASS intervention was conducted between December 2015 and April 2017 [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Two locations in the city of Rotterdam where the MASS intervention had not been implemented participated as control schools. These schools provided care as usual, which generally entailed a referral to a Youth Health Care professional on request of the student and, if possible, a consultation within the Care Advisory Team about the student [ 24 ]. Our intention was to include an equal number of students in the intervention and control condition, regardless of the number of participating schools.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this study, baseline data from the Medical Advice for Sick-reported Students (MASS) intervention study were used [30].…”
Section: Methodsmentioning
confidence: 99%